RESPONSE OF SOME GENOTYPES OF SOYBEAN TO ASCORBIC ACID SPRAYING - & et al., Al-Abodi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field experiment was conducted at the Experimental Farm, Department of Field Crops, College of Agriculture, University of Baghdad /Abu-Ghraib during the growing season of 2009 and 2010 to investigated the effect of spraying of ascorbic acid at three concentrations (0.5, 1.0 and 1.5) gm L-1 on some growth characters and yield of three genotypes of soybean (Sori, Lee and Snaea -2-), using RCBD with in split plot arrangement with three replications. The genotypes were in main plots while the concentrations of ascorbic acid were in sub plots. The results showed that the superiority of Sori genotype in branches No. (7.11 and 7.90) branch.plant-1, pods No. (153.44 and 187.43) pod.plant-1, pods weight (133.17 and 173.54) gm and 100 seed weight about 11.01 and 12.78 gm so gave highest plant yield about 91.11 and 95.19 gm.plant-1 for both season respectively. Spraying of ascorbic acid caused significant increase in most studied characters and the concentration 1.5 gm L-1 was superior in branches No. (6.49 and 6.84 branch.plant-1, pods No. (112.95 and 129.56) pod.plant-1, pods weight (101.42 and 118.58) gm and seeds per pod (2.64 and 2.70) seed.pod-1 so gave highest seed yield per plant about 76.82 and 83.90 gm.plant-1 for both season respectively. The best combination was Sori X 1.5 gm L-1 gave highest seed yield per plant about 101.51 and 108.88 gm.plant-1 for both season respectively. The conclusion from this study was: The different genotypes of soybean were different in their response to ascorbic acid spraying and the level 1.5 gm L-1 was the best for all the studied genotypes.